2005
DOI: 10.1136/emj.2003.010850
|View full text |Cite
|
Sign up to set email alerts
|

Does leucocytosis identify bacterial infections in febrile neonates presenting to the emergency department?

Abstract: Objective: This study was undertaken to evaluate the discriminatory power of the peripheral white blood cell (WBC) count to identify bacterial infections in a cohort of febrile neonates ((28 days of age) presenting to an emergency department. Methods: Retrospective medical record review using descriptive statistics and a receiver operating characteristic (ROC) curve. Neonates who presented to a tertiary care paediatric emergency department between 1 January 1999 and 22 August 2002, had a temperature >38˚C, und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 25 publications
2
34
1
4
Order By: Relevance
“…This is higher in infants aged 0-28 days (9-28%) than those 2-3 months old (7.1%) [2][3][4][5][6][7][8][9]15,16]. We found the overall rate of SBI was high (38.4%) and our findings confirmed that SBI was seen more frequent in the neonatal period.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is higher in infants aged 0-28 days (9-28%) than those 2-3 months old (7.1%) [2][3][4][5][6][7][8][9]15,16]. We found the overall rate of SBI was high (38.4%) and our findings confirmed that SBI was seen more frequent in the neonatal period.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, UTI was found higher and reported that 14-21.3 percent in febrile neonatesthat means UTI affects approximately 1 in 6 febrile neonates [2][3][4][5][6][7][8][9][10][11]18]. In our study, UTI incidence was found similarly the most common etiology of fever in neonatal period.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The clinical signs of leukemia may be evident at birth with hepatosplenomegaly, petechiae and ecchymosis [7]. Leukemic cell infiltration into the skin (leukemia cutis) is commonly found when the disease appears at birth and has also been noted in still born premature infants with leukaemia [8]. Patients with hyperleukocytosis should be closely monitored for its well-known complications like acute respiratory failure, pulmonary hemorrhage, CNS infarction, hemorrhage, splenic infarction, myocardial ischemia, renal failure due to renal vessel leukostasis [1,5].…”
Section: Discussionmentioning
confidence: 99%